Do Social Cognition Deficits Recover with Abstinence in Alcohol‐Dependent Patients?. (1st February 2021) - Rupp, Claudia I.; Junker, David; Kemmler, Georg; Mangweth‐Matzek, Barbara; Derntl, Birgit
Abstract : Background: Despite growing evidence of the presence and clinical relevance of deficits in social cognition in individuals with alcohol use disorder (AUD), less is known about the potential of "natural" recovery with abstinence in this neurocognitive domain. This study investigated the abstinence‐based recovery of neurocognitive social abilities in alcohol‐dependent patients (ADP) using a prospective longitudinal design with follow‐up assessment under controlled conditions of abstinence during alcohol dependence inpatient treatment. Methods: Seventy‐seven participants (42 ADP and 35 healthy controls [HC]) performed social cognition testing, including facial emotion recognition, perspective taking, and affective responsiveness twice (baseline/T1 and follow‐up/T2) during comparable follow‐up periods. Assessment of social cognition in abstinent ADP was conducted at the beginning (T1; within the first 2 weeks) and at the end (T2; within the last 2 weeks) of long‐term (2 months) abstinence‐oriented alcohol dependence inpatient treatment. Only patients abstinent for >14 days (last heavy drinking day >21 days) at baseline (T1) and who remained abstinent at follow‐up (T2) were included. Results: ADP, who on average were nearly 2 months abstinent at T1, showed poorer social cognition in all 3 areas (emotion recognition, perspective taking, and affective responsiveness) than HC. There was no difference between groups on the change in performance over time, and group differences (ADP vs. HC) remained significant at T2, indicating persistent social cognition deficits in ADP following controlled abstinence during inpatient treatment. Conclusions: Our findings indicate no natural recovery of social cognition impairments in ADP during an intermediate to long‐term period of abstinence (2+ months), the usual active treatment phase. Research aimed at developing interventions that focus on the improvement of social cognition deficits (e.g., social cognition training) and determining whether they benefit short‐ and long‐term clinical outcomes in AUD seems warranted. Abstract : This prospective longitudinal study found that deficits in social cognition in alcohol‐dependent patients persist despite alcohol abstinence during inpatient treatment. Novel interventions (e.g., adjunctive personalized neurocognitive rehabilitation therapy) targeting poor social cognition may be needed in addition to standard treatment for alcohol dependence.